Algoritmo iterativo para la planeación de la producción mixta basado en la función acumulativa de pertenencia - Figueroa García, Juan Carlos; Kalenatic, Dusko; López Bello, César Amilcar (Ingeniería, 2011)
This paper shows an application of a novel algorithm for Fuzzy Linear Programming (FLP) problems with both fuzzy technological coefficients and constraints, which deals with any kind of fuzzy membership functions for technological parameters and fuzzy linear constraints. The presented approach uses an iterative algorithm which finds stable solutions to problems with fuzzy parameter sinboth sides of an FLP problem. The algorithm is based on the soft constraints method proposed by Zimmermann combined with an iterative procedure which gets a single optimal solution.